(untitled) - Pendleton, Robert L. (New York, 1962)
In an age of national self-determination, when country after country is gaining or regaining autonomy, Thailand is all but unique. Alone in Southeast Asia, Thailand has maintained sovereign power within the historic past; while the greater part of Asia and Africa, in recent centuries, have been parts of European empires, Thailand has hardly been invaded, and never conquered, by Western arms. Partly because Thailand has never been under Western control, this nation is, perhaps, less well known in the Western world than almost any other. Yet the winds of change have affected Thailand no less because she has maintained political autonomy; in some ways, indeed, Thailand's leaders have been the more ready to adopt new ideas, new techniques, new ways of looking at resources, because nationalism there has been less of an issue. The present shape of the Thailand economy, the patterns of its recent growth, and the paths it is likely to follow in the future hold interest, then, not merely for their own sake, but as a possible indicator of how the whole of the non- colonial but still underdeveloped world may in time react, when present political feeling no longer obscures the longer-range problems of economic growth.
Keywords: Thailand,Thái Lan; Description and travel,Du lịch và miêu tả